2016
DOI: 10.1371/journal.pntd.0004896
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Dynamics of Visceral Leishmaniasis in the Indian Subcontinent – A Systematic Literature Review

Abstract: BackgroundAs Bangladesh, India and Nepal progress towards visceral leishmaniasis (VL) elimination, it is important to understand the role of asymptomatic Leishmania infection (ALI), VL treatment relapse and post kala-azar dermal leishmaniasis (PKDL) in transmission.Methodology/ Principal FindingWe reviewed evidence systematically on ALI, relapse and PKDL. We searched multiple databases to include studies on burden, risk factors, biomarkers, natural history, and infectiveness of ALI, PKDL and relapse. After scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 149 publications
3
78
0
1
Order By: Relevance
“…TDR-supported research showed a more than 8-fold underestimation of disease burden [83, 84], an annual VL incidence that was up to 22 times higher than the elimination target [85], a 6% case fatality rate (Table 3) [86], and established a baseline for the attack phase of the VL elimination programme. Furthermore, TDR-supported epidemiological research defines and corroborates the role of poverty, caste, literacy, housing condition, proximity to vegetation, water bodies, livestock, and sleeping habits in influencing exposure to the risk of VL, which helped understanding of human–vector transmission and to inform vector-control strategies for VL elimination [8792]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TDR-supported research showed a more than 8-fold underestimation of disease burden [83, 84], an annual VL incidence that was up to 22 times higher than the elimination target [85], a 6% case fatality rate (Table 3) [86], and established a baseline for the attack phase of the VL elimination programme. Furthermore, TDR-supported epidemiological research defines and corroborates the role of poverty, caste, literacy, housing condition, proximity to vegetation, water bodies, livestock, and sleeping habits in influencing exposure to the risk of VL, which helped understanding of human–vector transmission and to inform vector-control strategies for VL elimination [8792]. …”
Section: Resultsmentioning
confidence: 99%
“…The strategy needs a paradigm shift from preventing disease to preventing infection and interrupting transmission. The infectiousness of asymptomatic individuals infected with Leishmania , markers for progression to VL disease, the role of domestic animals in transmission, and the potential of PKDL as a reservoir for infection need to be better understood [92, 125127]. The implications of HIV coinfection with VL for treatment failure and relapse, transmission dynamics, and development of parasite resistance to drugs need to be studied further, and strategies need to be developed and tested as appropriate [42].…”
Section: Discussionmentioning
confidence: 99%
“…We calculated the sample size taking into account only one explanatory variable, therefore the statistical power for detecting significant associations could be lower when analyzing multiple variables simultaneously. One particular challenge in VL field studies is the unknown number of asymptomatic cases [33]. However, as the ratio between clinical VL cases and asymptomatic cases is fairly constant, we can take the socio-economically more important clinical VL cases as an indicator of VL transmission.…”
Section: Discussionmentioning
confidence: 99%
“…In general terms, this and related studies on preventive measures are important for the maintenance of the VL elimination achievements [33,34] which are not only threatened by the decrease of Public Health activities after reaching the elimination goal (abandoning vector control and early case detection and treatment) but also the challenges of environmental and climate change which contribute to the spread of VL [16].…”
Section: Discussionmentioning
confidence: 99%
“…Spleen becomes palpable only after being enlarged twice to thrice [40]. Therefore, transmission potential of such cases should also be considered [41,42]. Ultrasonographic detection of sub-palpable splenomegaly and bone marrow/ intercostal splenic parasitology has been found to provide additional yield of kala-azar cases [43].…”
Section: Kala-azar Transmission After Outbreak Responsementioning
confidence: 99%